A Neutrosophic Topological Model for Analyzing Higher Education Internationalization Competence through Cross-Cultural Communication and Collaboration - Zesi Fan (Neutrosophic Sets and Systems)
This paper presents a new way to measure internationalization competence using a neutrosophic topological model, focusing on how people communicate and work together across different cultures. We use neutrosophic logic, which considers truth, uncertainty, and falsehood, to represent each person’s skills as a mathematical set. These sets help us analyze how cultural abilities combine or overlap during collaboration. By applying N-norm and N-conorm operations, we calculate shared skills and overall team strengths. The model also identifies gaps in competence through a complement operation. We provide clear equations and examples to show how the model works in practice. This approach offers a precise tool for assessing cross-cultural skills and lays the groundwork for future studies on cultural collaboration.